Distributive justice and the effect of benefit types on job performance within federal GLC in Sarawak, Malaysia - Ismail Azman, Ong Clara, Guat Leng, Yeop Yunus Nek Kamal, (N/A, 2009)
Distributive justice and the effect of benefit types on job performance within federal GLC in Sarawak, Malaysia by Ismail Azman, Ong Clara, Guat Leng, Yeop Yunus Nek Kamal,